Access to finance: exploring barriers to entrepreneurship development in SMEs - Mohd Khan, Shazida Jan; Anuar, Abdul Rahim (IGI Global, 2018)
Over the years, Malaysian government has attributes to a number of supports programs to the small and medium enterprises (SMEs) sector. These includes the involvement of several government agencies, at both the federal and state levels, providing variety of programs to SMEs sector in achieving sustainable levels of growth and development. A well-developed financial infrastructure that is able to meet the diverse financing needs of SMEs is essential to support the competitiveness and continuous growth of SMEs.